Desarrollo e implementación de una página web que controle los procesos tributarios para Ecofin, usando tecnología open source (Linux, Openxava, Postgresql) y empleando la metodología XP - Lalangui Díaz, Mayra Lastenia (2014)
This thesis project aims to implement a web application for ECOFIN to manage efficiently the tax control processes in the shortest possible time, to successfully meet each of the requirements of the ECOFIN OpenXava framework that is useful for automating processes employed management and taxation, as manager database is PostgreSQL used as it provides stability and reliability, and methodology development software Xtreme Programming (XP) that allows frequent meetings with the user clearly informed of all needs presented the company.